Sex Reversal and Performance in Fitness-Related Traits During Early Life in Agile Frogs - Bókony, Veronika; Ujhegyi, Nikolett; Mikó, Zsanett; Erös, Réka; Hettyey, Attila; Vili, Nóra; Gál, Zoltán; Hoffmann, Orsolya Ivett; Nemesházi, Edina (Frontiers in Ecology and Evolution, 2021)
Sex reversal is a mismatch between genetic sex (sex chromosomes) and phenotypic sex (reproductive organs and secondary sexual traits). It can be induced in various ectothermic vertebrates by environmental perturbations, such as extreme temperatures or chemical pollution, experienced during embryonic or larval development. Theoretical studies and recent empirical evidence suggest that sex reversal may be widespread in nature and may impact individual fitness and population dynamics. So far, however, little is known about the performance of sex-reversed individuals in fitness-related traits compared to conspecifics whose phenotypic sex is concordant with their genetic sex. Using a novel molecular marker set for diagnosing genetic sex in agile frogs (Rana dalmatina), we investigated fitness-related traits in larvae and juveniles that underwent spontaneous female-to-male sex reversal in the laboratory. We found only a few differences in early-life growth, development, and larval behavior between sex-reversed and sex-concordant individuals, and altogether these differences did not clearly support either higher or lower fitness prospects for sex-reversed individuals. Putting these results together with earlier findings suggesting that sex reversal triggered by heat stress may be associated with low fitness in agile frogs, we propose the hypothesis that the fitness consequences of sex reversal may depend on its etiology.